An Analysis of Moral Value in “The Alchemist” Novel Written By Paulo Coelho - suhendar, suhendar; Ismi, Diyaa Naurah Mizanti; Budiarto, Budiarto (STIBA IEC JAKARTA, 2024)
Accordingly, in a literary work, there are normally certain hidden messages to be conveyed from the researcher to the reader or what are so-called as moral values. In relation to which, The Alchemist novel is deemed to be one of literary works that conveys the message of education, culture, interaction in the society, religion, and moral values in life. In view of that, these things are considered to be the urgency of this research. This research aims to identify and analyze the moral values and the intrinsic elements in The Alchemist novel and the way the researcher presents the aforesaid literary work. This research applies qualitative method with descriptive approach. As for the data source thereof, it is the primary data namely The Alchemist novel by Paulo Coelho which took several steps to gather the data trough among the other things reading the book carefully, identifying the data to be analyzed, and finally finding the result thereof. Meanwhile, the data collection was gathered from the secondary data such as international journal, text book, and internet. The findings reveal that there are several moral values and intrinsic elements clearly presented in The Alchemist novel namely responsibility, obligation, pure heart, formality, bravery, humbleness, honesty, steadfastness, and sympathetic. Subsequently, the intrinsic elements are divided into several parts such as plot, theme, character, setting, and point of view.